The long road from teacher professional development to student improvement: A school-wide professionalization on self-regulated learning in primary education. Issue 6 (2nd November 2022) - Heirweg, Sofie; De Smul, Mona; Merchie, Emmelien; Devos, Geert; Van Keer, Hilde
ABSTRACT: Notwithstanding the value of self-regulation, different studies evidence that self-regulated learning (SRL) is still insufficiently ingrained in schools and that teachers only rarely promote it among their students. Therefore, the current study reports on a one-year school-wide professional development programme (PDP). A quasi-experimental pre-test-post-test design was used with 10 schools randomly assigned to the experimental group (EG) and 10 schools to the control group (CG). To analyse how far the effects of the PDP reach, the impact on teachers' SRL beliefs, self-efficacy, their SRL promotion behaviour and students' SRL competences and achievement scores was investigated. Data were gathered from 40 fifth and sixth grade teachers (nEG = 22, nCG = 18) and their 747 upper primary school students (nEG = 448, nCG = 299). Analyses of covariance were used to study teacher-level effects, while multilevel analyses were adopted to investigate student-level effects. Results indicate that the PDP generated an increase in teachers' SRL promotion, while no significant effect on their SRL beliefs and SRL self-efficacy could be found. Similarly, results overall indicate the absence of a desired intervention effect at the student level. Different explanations for the present results and recommendations for future research are discussed.